Microsatellite analysis revealed genetic diversity and population structure among Chinese cashmere goats - Di, R.; Vahidi, S.M.F.; Ma, Y.H.; He, X.H.; Zhao, Q.J.; Han, J.L.; Guan, Wei-Jun; Chu, M.X.; Sun, W.; Pu, Y.P. (Wiley, 2011)
Most cashmere goats are found in northern China and Mongolia. They are regarded as precious resources for their production of high quality natural fibre for the textile industry. It was the first time that the genetic diversity and population structure of nine Chinese cashmere populations has been assessed using 14 ISAG/FAO microsatellite markers. In addition, two Iranian populations and one West African goat population were genotyped for comparison. Results indicated that the genetic diversity of Chinese cashmere goats was rich, but less than those of the Iranian goat populations. All pairwise FST values between the Chinese cashmere goat populations reached a highly significant level (P < 0.001), suggesting that they should all be considered as separate breeds. Finally, clustering analysis divided Chinese cashmere goats into at least two clusters, with the Tibetan Hegu goats alone in one cluster. An extensive admixture was detected among the Chinese goat breeds (except the Hegu), which have important implications for breeding management.